2012
DOI: 10.1177/030006051204000610
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase B Phosphorylation Correlates with Vascular Endothelial Growth Factor A and Microvessel Density in Gastric Adenocarcinoma

Abstract: Objective: The signalling molecule protein kinase B (Akt) modulates many cellular processes. Phosphatidylinositol 3-kinase (PI3K)/Akt signalling pathways play important roles in tumour angiogenesis. The aim of this study was to determine the role of phosphorylated Akt (pAkt) in angiogenesis and its correlation with vascular endothelial growth factor (VEGF)-A in gastric adenocarcinoma. Methods: Tumour tissue and matched healthy gastric mucosa were obtained from patients undergoing surgical resection of gastri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…[ 12 - 14 ]. Our previous study confirmed that p-Akt involved in angiogenesis of gastric adenocarcinoma and Akt activation may contribute to angiogenesis via VEGF-A up-regulation [ 15 ]. In this study, the positive staining rates of p-Akt and p-mTOR in 55 cases of gastric cancer were 74.54% and 85.45% respectively.…”
Section: Discussionsupporting
confidence: 70%
“…[ 12 - 14 ]. Our previous study confirmed that p-Akt involved in angiogenesis of gastric adenocarcinoma and Akt activation may contribute to angiogenesis via VEGF-A up-regulation [ 15 ]. In this study, the positive staining rates of p-Akt and p-mTOR in 55 cases of gastric cancer were 74.54% and 85.45% respectively.…”
Section: Discussionsupporting
confidence: 70%
“…The PI3K/Akt pathway is frequently activated in gastric carcinogenesis and vital to gastric cancer development [ 18 ]. This pathway was found to be activated by H. pylori infection both in vivo and in vitro , which is consistent with previous studies [ 17 , 19 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The PI3K/Akt pathway is downstream of PTEN [ 14 ] and is frequently activated in gastric carcinogenesis and vital to gastric cancer development [ 41 ]. This pathway was found to be activated by H. pylori infection both in vivo and in vitro , which is consistent with previous studies [ 9 , 10 , 35 - 40 , 42 ].…”
Section: Discussionmentioning
confidence: 99%